Using of Artificial Intelligence Techniques and for Improving the Accuracy of Financial Reports: Applied study in Asia cell Telecommunications Company - Forat Sattar Hassoon (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The research aims to clarify the relationship between artificial intelligence and the future of the accounting profession, and to clarify the knowledge foundations of artificial intelligence and the future of the accounting profession and the application of the term artificial intelligence in the future of the accounting profession and highlight the position of the term artificial intelligence for the economic unit of the research sample, which is Asia cell Iraq Company. The research relied on the collection of data related to the theoretical aspect on a group of Arab and foreign sources related to the subject under research from books, research, studies, theses and university theses, as well as research and periodicals published on the Internet, as for the applied side, the research relied on field visits to the research sample and personal interviews with managers and officials in the research sample as well as to the accounting of the force the research reached a set of conclusions, the most important of which was that the subject of artificial intelligence itself is one of the contemporary topics that did not find any interest at the conceptual, practical and even academic levels, at least at the level of libraries and scientific research centers. After the results of the electronic field surveys showed that the Arab and Iraqi libraries are devoid of any author or detailed study on the subject, and in conclusion, the research reached a set of recommendations, the most important of which was the need to give the artificial intelligence variable greater research attention as one of the intellectual dialectics in contemporary literature in the field of accounting management and to highlight its role in achieving sustainable artificial advantage in the business environment.